FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KUALITAS HASIL PEMERIKSAAN AUDITOR SEKTOR PUBLIK - Badjuri, Achmad (Proceeding SENDI_U, 2015)
The purpose of this research is to analyse the influence of independency, integrity,professionalism, competency and compliance code of conduct on the quality of audit performedby the auditors of Audit Board the Republic of Indonesia Representatives of Central JavaProvince. The population of this research consisted of all auditors who have completedEducation and Training for Functional Position of Certified Auditors (JFP) and a minimally 2-year experience as auditors. The primary data was collected by administering questionnaires tothe respondents and the analysis was performed employing the multiple regression model. Theresult showed that integrity, professionalism and compliance with the code of conduct have apositive and signifiant impact on the audit quality, while independency and competency do nothave a positive impact on audit quality.Keywords: independency, integrity, professionalism, competency, compliance code of conduct,quality of audit.